Chapter New 'Excavations' in the Pergamon-Museum and in the Gipsformerei of Berlin and New Elements for the Study of the Decorative Programme of Kammer B in Yazılıkaya - Marazzi, Massimiliano (Studia Asiana, 2023)
Based on the work conducted during winter 2017 both on casts of the Hittite reliefs exhibited at the Pergamon-Museum and the original matrices of the Humann casts (1892) kept at the Gipsformerei in Berlin/Charlottenburg, a series of results are presented regarding the sculptural decoration programme present in the Yazılıkaya rock sanctuary. In addition, the exhibition and publication of a series of casts of Hittite reliefs on the occasion of the exhibition Royaumes Oubliés, held in Paris in 2019, made it possible to provide some insights into the history of the casts made by E. Chantre on the occasion of his Mission en Cappadoce in 1893-94